Profiling of differentially expressed genes in human Gastric carcinoma by cDNA expression array - Liu, Lian-Xin (World J Gastroenterol, 2002)
AIM: To investigate the expression of cancer related genes in gastric carcinoma (GC) through the use of Atlas Human Cancer Array membranes with 588 well-characterized human genes related to cancer and tumor biology. METHODS: Hybridization of cDNA blotting membrane was performed with (32)P-labeled cDNA probes synthesized from RNA isolated from gastric carcinoma and adjacent noncancerous gastric epithelial tissue. AtlasImage, which is a software specific to array, was used to analyze the result. RESULTS: The differentially expression cell cycle/growth regulator in GC showed a stronger tendency toward cell proliferation with 2.7-fold up-regulation of CK1. The promoter genes of apoptosis were down-regulated, including caspase-8 precursor, caspase-9 and caspase-10. Among the oncogene/tumor suppressor genes, ABL2 was down-regulated. In addition, some genes were up-regulated, including matrix metalloproteinse 2 (MMP-2), MMP-16 (MT3-MMP), SKY, CD9 and semaphorin V. A number of genes were down-regulated, including neuroendocrine-dlg (NE-dlg), retinoic acid receptor gamma and tumor suppressor DCC colorectal. In general, The expression of the cancer progression genes were up-regulated, while the expression of anti-cancer progression genes were down-regulated. CONCLUSION: Investigation of these genes should help to disclose the molecular mechanism of the onset, progression and prognosis of GC. Several genes are reported herein to be altered in GC for the first time. The quick and high-throughout method of profiling gene expression by cDNA array provides us with an overview of key factors that may involved in GC, and may aid the study of GC carcinogenesis and provide molecular targets for diagnosis and therapy. The precise relationship between the altered genes and gastric carcinogenesis is a matter for further investigation.